Knowledge Sharing in Closed-Loop Supply Chain Management - Shu-San Gan (International Journal of Industrial Research and Applied Engineering, 2017)
In the recent decades, closed-loop supply chain has been studied extensively due to the increased concern on sustainable development. It integrates forward and reverse flows where the collaborative supply chain takes place. Knowledge management is one important part of an organization that can improve the effectiveness of the processes within the organization. Knowledge sharing is significant in a collaborative supply chain since it affects the organizational performance and competitive advantage. The complexity in closed-loop supply chain can be managed better by encouraging knowledge sharing among the supply chain members. This paper presents a conceptual framework to implement knowledge sharing in a closed-loop supply chain management, for improving the CLSC members’ performance. The success factors have been identified, and a framework has been presented, it consists of knowledge flows, management aspect and socio-technical aspect.